The Changing Face of the Art Market: A Khalduni Approach - Yosra Jarrar (Ibn Haldun University, 2020)
The increasingly simulated dimension of reality has resulted in a major shift in the methods of providing services in the art market. As the market’s reliance on technology is transforming the ways through which artworks can be produced, accessed and “consumed”, both researchers and practitioners have been exploring the nature, scope and potentialities of utilizing virtual reality to help the market expand into new territories. Based on the existing literature, and using the method of textual descriptive analysis, this paper aims to relate the contemporary marketing models of the art market to Ibn Khaldun’s economic thought due to the important conceptual and pioneering role he played in the historic development of fundamental economic concepts that are still relevant in understanding different marketing implications today. It also examines whether the VR market would guarantee a higher level of morality in the way art is presented and protected keeping in mind the threats of cyber-crimes and digital piracy.